2020
DOI: 10.1364/oe.396108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high pulse intensity and chirp in two-dimensional electronic spectroscopy of an atomic vapor

Abstract: The effects of high pulse intensity and chirp on two-dimensional electronic spectroscopy signals are experimentally investigated in the highly non-perturbative regime using atomic rubidium vapor as clean model system. Data analysis is performed based on higher-order Feynman diagrams and non-perturbative numerical simulations of the system response. It is shown that higher-order contributions may lead to a fundamental change of the static appearance and beating-maps of the 2D spectra and that chirped pulses enh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Before we proceed, let us notice that, so far, we described the action of the laser pulses on the atoms non-perturbatively in the pulse area ϑ. Strong pulses (e.g., ϑ ≈ π) induce a nonlinear response of the atoms [19,53] and can be used as a control and diagnostic tool in electronic spectroscopy [54,55]. Furthermore, we have shown that strong pulses substantially modify the MQC signals [42].…”
Section: Ultrashort Time Scale-atom-laser Interactionmentioning
confidence: 99%
“…Before we proceed, let us notice that, so far, we described the action of the laser pulses on the atoms non-perturbatively in the pulse area ϑ. Strong pulses (e.g., ϑ ≈ π) induce a nonlinear response of the atoms [19,53] and can be used as a control and diagnostic tool in electronic spectroscopy [54,55]. Furthermore, we have shown that strong pulses substantially modify the MQC signals [42].…”
Section: Ultrashort Time Scale-atom-laser Interactionmentioning
confidence: 99%
“…Typically, weak-field signals are measured; that is, in 2WM, 4WM, or 6WM experiments each pulse interacts with the system only once. 95,96,588,658−660 Population-detected signals of atomic 493 and molecular 661−663 systems have also been measured in the strong-field regime.…”
Section: General Considerationsmentioning
confidence: 99%
“…A number of femtosecond 4WM experiments revealed that richer information on the photoinduced dynamics in atomic vapors, polyatomic chromophores, multichromophore aggregates, and nanosystems can be obtained by applying more intense laser pulses (see refs for reviews). On the theoretical side, a variety of simulations of 4WM signals beyond the limit of weak system–field coupling have been reported. ,,,, Single-molecule femtosecond spectroscopy of individual chromophores and antenna complexes , also usually requires strong pulses.…”
Section: Nonperturbative Calculation Of the Nonlinear Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Originated in nuclear magnetic resonance [5], the concept of multi-dimensional Fourier-transform spectroscopy has been implemented in the optical region using femtosecond lasers and developed into a powerful tool to study energy level structures, couplings, and dynamics in a variety of complex systems such as proteins [6], photosynthetic systems [7,8], semiconductor quantum wells [9][10][11][12][13], quantum dots [14][15][16][17], 2D mate-rials [18,19], perovskites [20,21], atomic vapors [22][23][24][25][26][27][28][29][30][31][32][33][34][35], and weakly-bound molecules on helium nanodroplets in a molecular beam [36]. Particularly, double-quantum 2DCS provids an extremely sensitive background-free detection of dipole-dipole interactions in both potassium (K) [25,30] and rubidium (Rb) [27,30] atomic vapors.…”
mentioning
confidence: 99%